'Subjective Europeanization': do inner-European comparisons affect life satisfaction?. Issue 2 (15th March 2019) - Lahusen, Christian; Kiess, Johannes
ABSTRACT: Research in the social sciences has shown recurrently that life satisfaction varies across countries. More recently, the question was raised whether Europeans are comparing living conditions in European countries, and whether these comparisons are affecting the way they assess their personal situation. The paper uses original survey data from nine European countries in order to answer these questions. We analyze the way European citizens assess the living conditions in the various countries under analysis. And we test whether assessments of other countries are significantly interrelated with reported levels of life satisfaction. Finally, we measure the extent to which these effects hold if other reference groups (friends, neighbors, own country) and individual socio-demographic traits are included in the analysis. Our findings paint a mixed picture. Assessing living conditions in other European countries is widely diffused and attests a marked 'cognitive Europeanization'. However, comparisons with other countries play a less relevant role for reported life satisfaction, when compared to the assessment of the own national economy and the own household situation. Moreover, Switzerland as a non-EU-member is a more significant target than most other EU-members, attesting that we are rather speaking of a European frame of reference, than an EU-related one.